Bone Mineral Density is Negatively Associated with Risk of All-Cause and Cardiovascular Mortality among Adults with Type 2 Diabetes Mellitus: A Cross-sectional Study of the NHANES 2005–2010, 2013–2014 - Li, Haipeng; Wang, Baolong; Xu, Dongshuo; Zhang, Jialu; Wang, Changhui (Reviews in cardiovascular medicine, 2024)
Background: With ageing and lifestyle changes, the coexistence of osteoporosis and type 2 diabetes (T2DM) is becoming more common, which greatly increases patient disability and mortality. However, the association of low bone mineral density (BMD) with cardiovascular disease (CVD) and all-cause mortality in T2DM patients have not been conclusively established. Methods: Using the National Health and Nutrition Examination Survey (NHANES) to obtain a nationally representative sample of the US population, we sought to determine the independent and incremental value of low BMD, particularly in patients with osteoporosis in assessing all-cause and CVD mortality in adults with T2DM. Results: We demonstrated that increased BMD was significantly related to decreased mortality from all-causes and CVDs among US adults with T2DM. In addition, we found that, after multivariate adjustment, osteoporosis and osteopenia were independently associated with an increased risk of all-cause and CVD mortality in T2DM patients at long-term follow-up. Conclusions: The clinical diagnosis of osteopenia or osteoporosis in adults with T2DM provides independent prognostic value for CVD and all-cause mortality.